Os Nahua: Língua e Cultura do Século XVI até o Presente: Language and Culture from the Sixteenth Century to the Present - Lima, Antonio Pedro, Jr. (Horizonte, 2025)
Brokaw, Galen; García, Pablo Loaeza (Eds.). "Os Nahua: Língua e Cultura do Século XVI até o Presente" The Nahua: Language and Culture from the Sixteenth Century to the Present. Denver: University Press of Colorado, 2024, 313p. ISBN: 978-1-64642-577-8